A Case Report: Unusual Manifestation of MIS-C with Acute Abdomen Caused by Gut Perforation - Ihsan, Indra; Mayetti, Mayetti; Yusuf, Yusirwan (Health and Medical Journal, 2024)
Background: Gastrointestinal symptoms are common presenting features of multisystem inflammatory syndrome in children (MIS-C) and can overlap with other abdominal symptoms. Case Report: We reported A case of a 2-year-old girl who was hospitalized with MIS-C and had abdominal pain symptoms which got worse day by day. Abdominal x-ray revealed gut perforation and she was consulted by the pediatric surgeon and then underwent an emergency exploratory laparotomy and intraoperative findings showed a perforation in the caecum area. Conclusion: MIS-C can induce acute gut perforation and in the pandemic era MIS-C should be considered in the differential for a patient with acute abdominal symptoms.